سنڌي ادب ۾ ترجمي جي اهميت ۽ ڪردار The Significance and Role of Translation in Sindhi Literature - Latif, Abdul (Social Science Review Archives, 2025)
Translation is a medium, by which the original meaning of the foreign language is transformed in a way which is easy to comprehend. Translation, indeed is the second name of creation. Modern critics, call that genre a creation. Translation is a difficult art than that of traditional creative works. It is accomplished after thorough observation. Human, social, political and educational development bank on observations. Social changes occur having studied other nation’s literacy works, which is inter connected with observation. For this translation plays its vital role. If we make a comparison between European and Asian literature with classical touch, the latter has left and untold influence on the former, and the credit goes to translation. Undoubtedly without the art of translation, intellectual upheaval is a question of the question. It is rightly said that the key to literacy treasure is translation. It is beyond doubt that the ocean of literature can only be surpassed by the cruise of translation.